Professional Ethics and the Lawyer’s Duty to Self - John J. Flynn (Washington University Law Quarterly, 1976)
This Article asserts that although much attention has been paid to immoral conduct and the means to prevent it, the greater hazard to lawyers generally is that of amoral conduct. The appropriate safeguard against amorality is greater concern for the lawyer’s duty to self.
Keywords: Legal ethics